2003
DOI: 10.1029/2003ja009956
|View full text |Cite
|
Sign up to set email alerts
|

Role of unstable sporadic‐E layers in the generation of midlatitude spread F

Abstract: [1] There is growing experimental evidence to suggest that mesoscale spread F is linked to the occurrence of midlatitude coherent backscatter from patchy sporadic-E layers, which are unstable to the gradient-drift and Farley-Buneman plasma instabilities. To validate this suggestion, we have compared E-region backscatter and spread-F ionosonde recordings from about 100 days of joint operation during summer and found a one-to-one relation in the occurrence of both phenomena. Also, midlatitude backscatter studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
107
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 27 publications
(63 reference statements)
5
107
0
Order By: Relevance
“…The electrodynamical coupling between the nighttime midlatitude ionospheric E s and F region have been invoked as an explanation for the large polarization electric fields observed in the F region and the consequent uplifts of the F layer which causes spread F [Tsunoda and Cosgrove, 2001]. Haldoupis et al [2003] proposed a mechanism for spread F development in the midlatitude ionosphere driven by northward-upward electric fields, which are generated from a meridional polarization field inside an unstable E s layer and maps to the F region via field lines. Cosgrove and Tsunoda [2004] derived a dispersion relation that describes the coupling behavior between E s layer and Perkins instability.…”
Section: Discussionmentioning
confidence: 99%
“…The electrodynamical coupling between the nighttime midlatitude ionospheric E s and F region have been invoked as an explanation for the large polarization electric fields observed in the F region and the consequent uplifts of the F layer which causes spread F [Tsunoda and Cosgrove, 2001]. Haldoupis et al [2003] proposed a mechanism for spread F development in the midlatitude ionosphere driven by northward-upward electric fields, which are generated from a meridional polarization field inside an unstable E s layer and maps to the F region via field lines. Cosgrove and Tsunoda [2004] derived a dispersion relation that describes the coupling behavior between E s layer and Perkins instability.…”
Section: Discussionmentioning
confidence: 99%
“…Tsunoda and Cosgrove (2001) suggested that there is a large feedback polarization electric field mapped from the E layer and contributing to the F region irregularities. To validate the linkage between spread F and Es, Haldoupis et al (2003) investi- gated recordings of ionosonde in summer and found a precise corresponding relation between spread F and the patchy, sporadic E layer. They concluded that the enhanced electric field set up in unstable Es could easily map up to F region and trigger gradient drift instability to form mid-latitude irregularities.…”
Section: Discussionmentioning
confidence: 99%
“…Each image has been standardized so that north is at the top and east is to the right (after Kelley et al, 2002, reproduced with permission of Elsevier). Haldoupis et al (2003) and Kelley et al (2003) showed experimentally that the E-and F-regions are closely coupled in this process. Theoretical work has lagged far behind experiments.…”
Section: Introductionmentioning
confidence: 99%